2018
DOI: 10.1002/mbo3.745
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high‐grain diet feeding on mucosa‐associated bacterial community and gene expression of tight junction proteins in the small intestine of goats

Abstract: The objective of this study was to investigate the impact of a high‐grain (HG) diet on the microbial fermentation, the composition of the mucosa‐associated bacterial microbiota, and the gene expression of tight junction proteins in the small intestine of goats. In the present study, we randomly assigned 10 male goats to either a hay diet ( n = 5) or a HG diet (56.5% grain; n = 5) and then examined changes in the bacterial community using Illumina MiSeq sequencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…Interestingly, Basal rations addition of CSH or ADY either significantly decreased the abundance of Eubacterium coprostanoligenes . Study also found that goats fed high-grain diet had the higher intestinal abundance of Eubacterium coprostanoligenes compared to the goats fed a hay diet (Liu et al, 2018). This genus population may have a negative relationship with dietary nutrition levels.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, Basal rations addition of CSH or ADY either significantly decreased the abundance of Eubacterium coprostanoligenes . Study also found that goats fed high-grain diet had the higher intestinal abundance of Eubacterium coprostanoligenes compared to the goats fed a hay diet (Liu et al, 2018). This genus population may have a negative relationship with dietary nutrition levels.…”
Section: Discussionmentioning
confidence: 93%
“…Notably, members of families Ruminococcaceae and Christensenellaceae are relatively enriched in the feces of domestic lambs with high feed efficiency versus those with low feed efficiency, and ruminal Lachnospiraceae are negatively associated with feed efficiency. Some bacterial lineages may be conserved www.nature.com/scientificreports www.nature.com/scientificreports/ because they are ubiquitous in the environment or are highly adept at dispersal; however, based on their inferred relationship with ruminant nutrition [55][56][57]59 and (in the case of Christensenellaceae) host heritability 58 , we propose that family Ruminococcaceae, family Lachnospiraceae, and genus Christensenellaceae R7 group are conserved across bighorn sheep populations due to an adaptive relationship with their host.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial taxa containing the largest numbers of conserved clades belonged to family Ruminococcaceae, family Lachnospiraceae, and genus Christensenellaceae R7 group, all of which are members of order Clostridiales and phylum Firmicutes. Families Ruminococcaceae and Lachnospiraceae are dominant fecal bacterial families in domestic sheep 54 , and all three taxa are known to be important rumen symbionts that associate positively with consumption of high-forage diets 55,56 . Members of family Ruminococcaceae are known to play an important role in initiating the breakdown of plant fiber in the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies by our group and others, the HC diet appeared to disrupt the balance of the ruminal microbiota in ruminants by Illumina MiSeq sequencing methods [ 9 , 24 , 25 ]. However, little information was available on microbial response of the small intestine to the HC diet using a high-throughput method [ 26 ]. In the present study, we used high-throughput 16S rRNA gene sequencing to assess the shifts in the microbial adaptation of goat’s ileum in response to a HC diet.…”
Section: Discussionmentioning
confidence: 99%